MANAGEMENT OF INFORMATION AND COMMUNICATION TECHNOLOGIES AND THEIR EFFECTS ON PROFESSIONAL SKILLS IN HIGHER EDUCATION INSTITUTIONS - Alberto Núñez Lira, Luis; Cecilia Uribe Hernández, Yrene; Dulvina Romero Díaz, Alejandra (Gênero & Direito, 2020)
The objective of this work was to evaluate the management of information and communication technologies (ICT) to determine the effects that they generate on professional skills in public educational institutions in Lima (Peru). The research was a quantitative approach, with a non-experimental cross-sectional and correlational design, using the survey technique and the questionnaire as an instrument. As a result, it was found that 71.8% of the management of information technologies positively affects the development of professional skills, with a bilateral significance of 0.002. Coming to the conclusion that teachers have empowered themselves with ICTs, generating a new way of interacting between teachers and students, breaking the limitations of the classroom; improving the teaching-learning processes, strengthening their capacities and achieving significant learning.